2019
DOI: 10.1111/nph.15970
|View full text |Cite
|
Sign up to set email alerts
|

The long and short of the S‐locus in Turnera (Passifloraceae)

Abstract: Distyly is an intriguing floral adaptation that increases pollen transfer precision and restricts inbreeding. It has been a model system in evolutionary biology since Darwin. Although the Slocus determines the long-and short-styled morphs, the genes were unknown in Turnera. We have now identified these genes.We used deletion mapping to identify, and then sequence, BAC clones and genome scaffolds to construct S/s haplotypes. We investigated candidate gene expression, hemizygosity, and used mutants, to explore g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(118 citation statements)
references
References 74 publications
6
112
0
Order By: Relevance
“…First, the dominant S ‐haplotype of the S‐morph comprises a hemizygous region of several genes absent from the s ‐haplotype of the L‐morph. Significantly, this appears to be a feature of the four genera investigated (Ushijima et al ., ; Yasui et al ., ; Kappel et al ., ; Cocker et al ., ; Shore et al ., ). Second, candidate genes controlling sex organ height have been identified in each genus.…”
Section: Genetic Architecturementioning
confidence: 97%
See 4 more Smart Citations
“…First, the dominant S ‐haplotype of the S‐morph comprises a hemizygous region of several genes absent from the s ‐haplotype of the L‐morph. Significantly, this appears to be a feature of the four genera investigated (Ushijima et al ., ; Yasui et al ., ; Kappel et al ., ; Cocker et al ., ; Shore et al ., ). Second, candidate genes controlling sex organ height have been identified in each genus.…”
Section: Genetic Architecturementioning
confidence: 97%
“…Studies of Linum have identified a candidate gene ( TSS1 ) controlling style length that is expressed in styles of the S‐morph but not the L‐morph (Ushijima et al ., ). In Turnera , three hemizygous candidate genes, TsBAHD , TsSPH1 and TsYUC6 , appear to determine, respectively, style, filament and anther characteristics in the S‐morph, but are absent from the L‐morph (Shore et al ., ). Significantly, both putative style length genes, TsBAHD and CYP734A50 in Turnera and Primula , respectively, have high homology to genes that inactivate brassinosteroids, known regulators of cell expansion.…”
Section: Genetic Architecturementioning
confidence: 97%
See 3 more Smart Citations